Approximation and online algorithms : 10th International Workshop, WAOA 2012, Ljubljana, Slovenia, September 13-14, 2012, Revised Selected Papers - Persiano, Giuseppe; Erlebach, Thomas (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed post workshop proceedings of the 10th International Workshop on Approximation and Online Algorithms, WAOA 2012, held in Ljubljana, Slovenia, in September 2012 as part of the ALGO 2012 conference event. The 22 revised full papers presented together with invited talk were carefully reviewed and selected from 60 submissions. The workshop covered areas such as geometric problems, online algorithms, scheduling, algorithmic game theory, and approximation algorithms.